Why does strawberry fruit weight distribution show positive skewness? A simulation model reveals the underlying processes of fruit production - Cao, Zhihao; Jiang, Zhenfeng; Liu, Guanghui; Wang, Yong; Qu, Hongchun (Frontiers in Plant Science, 2023)
It is widely accepted that the weight distribution of plant fruits conforms to a standard normal distribution. However, some overlooked evidence suggests that some fruits, including strawberries, exhibit positive skewness in fruit weight distribution. This intriguing observation has received limited attention thus far. To shed light on this phenomenon, we conducted a comprehensive simulation study utilizing greenhouse-grown strawberries as our research subject. We modelled the entire process from bee pollination to pollen fertilization on the stigma and fruit growth. The experimental results demonstrated the reliability of the proposed simulation model and revealed that the positive skewness of the fruit weight distribution was the result of the multiplication of several complex intermediate variable distributions, which led to an approximately lognormal distribution. The simulation model and the derived conclusions presented in this paper offer a plausible explanation for the weight distribution patterns observed in strawberry production systems. Furthermore, research results have the potential to be applied to other berry plants that undergo similar bee pollination processes, thereby expanding our understanding of fruit weight distributions across different species.